Standardization and Ecosystem Collaborative Development Strategies for Digital Industrial Platforms - Fuqiang, Guo (International Journal of Multidisciplinary Research, 2026)
With the development of the digital economy and the arrival of Industry 4.0, digital industrial platforms have become an important vehicle for promoting the transformation of the manufacturing industry. This paper uses a combination of literature review, case studies, and field investigation to explore the main factors in the standardization construction of digital industrial platforms and the mechanisms for ecological collaborative development. The results show that the current standardization construction of digital industrial platforms suffers from problems such as an incomplete standard system, poor interoperability between platforms, and inconsistent data formats, hindering the collaborative development of the platform ecosystem. Through in-depth research on typical digital industrial platforms both domestically and internationally, this paper systematically reviews the existing theoretical framework for the impact of climate change on agriculture, focusing on the potential mechanisms by which temperature fluctuations and changes in precipitation patterns affect wheat production. By integrating domestic and international literature from the past five years, this paper discusses the limitations and optimization directions of adaptive strategies, providing theoretical references for future research.